2009
DOI: 10.1590/s1677-04202009000100006
|View full text |Cite
|
Sign up to set email alerts
|

Water relations and organic solutes production in four umbu tree (Spondias tuberosa) genotypes under intermittent drought

Abstract: In order to evaluate changes in leaf water potential (ψw) and solute accumulation induced by intermittent drought, an research was performed under greenhouse conditions using four umbu tree genotypes (GBU 44, GBU 48, GBU 50 and GBU 68) and two water treatments (control and stressed by withholding water), with four replicates. The ψw was measured in four-hour intervals during a 24-hour period at the first stomatal closure and at the end of the experimental period. Carbohydrates, amino acids, protein and proline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 32 publications
2
27
0
Order By: Relevance
“…Recent studies indicate that the main function of amino acid accumulation may be related to the osmotic adjustment (Sircelj et al 2005, Silva et al 2009, Medeiros et al 2012. In the present work, increases were observed in amino acid concentrations in the water suppression treatment, what may attest the function of osmoregulation and/or osmoprotection of these compounds.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Recent studies indicate that the main function of amino acid accumulation may be related to the osmotic adjustment (Sircelj et al 2005, Silva et al 2009, Medeiros et al 2012. In the present work, increases were observed in amino acid concentrations in the water suppression treatment, what may attest the function of osmoregulation and/or osmoprotection of these compounds.…”
Section: Discussionsupporting
confidence: 64%
“…The accumulation of osmoregulators in response to drought is an important mechanism for maintaining cell turgor, contributing to alleviate the reduction of the water potential. Previous studies have observed an increase in solutes in sugarcane and other species under water-deficient conditions (Ashraf and Foolad 2007, Cha-um e Kirdmanee 2009, Silva et al 2009, Silva et al 2013. Nevertheless, only solute accumulation does not favour the tolerance to drought per se, but the pathway that leads to the mechanism of drought tolerance is strongly influenced by this factor (Hasegawa et al 2000, Medeiros et al 2012.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Under a temperature condition of 80°C, the activity of umbu POX is four times higher in crude exsudate then in the purified fraction. Since, xilopodium exsudates are rich in soluble sugars (Silva et al, 2009), is possible that these substances may be acting as a natural thermal protector for umbu POX. Other possibilities must be considered since for …”
Section: Resultsmentioning
confidence: 99%
“…The browning color atributed to this product may be related to oxidation of phenols by poliphenoloxidase or peroxidase, a common trouble viewed in food processing (Mousavizadeh and Sedaghathoor, 2011). Due to the formation of xylopodium and other characteristics, umbu plants are highly resistant to drought (Silva et al, 2009). A unique umbu tree is able to grow down into its roots near to two tons of xylopodium (Cavalcanti and Resende, 2006).…”
Section: Introductionmentioning
confidence: 99%